2017
DOI: 10.3390/f9010011
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Community and Ligninolytic Enzyme Activities in Quercus deserticola Trel. Litter from Forest Fragments with Increasing Levels of Disturbance

Abstract: Litter fungal communities and their ligninolytic enzyme activities (laccase, Mn-peroxidase, and lignin-peroxidase) play a vital role in forest biogeochemical cycles by breaking down plant cell wall polymers, including recalcitrant lignin. However, litter fungal communities and ligninolytic enzyme activities have rarely been studied in Neotropical, non-coniferous forests. Here, we found no significant differences in litter ligninolytic enzyme activities from well preserved, moderately disturbed, and heavily dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 86 publications
(113 reference statements)
1
6
0
Order By: Relevance
“…Taxonomically, the fungi detected belonged mostly to the Ascomycota, less often to the Basidiomycota and occasionally to the Mucoromycota. The results are consistent with earlier findings on fungal communities from litter [47,48,50,51,89,90], although the relative occurrences of Ascomycota and Basidiomycota depend on the stage of decomposition of the substrate. Ascomycota are usually relatively more abundant in the early stages of decomposition while Basidiomycota increase over time, becoming most frequent at the advanced decomposition stage [48,51,[89][90][91].…”
Section: Fungal Diversitysupporting
confidence: 92%
See 1 more Smart Citation
“…Taxonomically, the fungi detected belonged mostly to the Ascomycota, less often to the Basidiomycota and occasionally to the Mucoromycota. The results are consistent with earlier findings on fungal communities from litter [47,48,50,51,89,90], although the relative occurrences of Ascomycota and Basidiomycota depend on the stage of decomposition of the substrate. Ascomycota are usually relatively more abundant in the early stages of decomposition while Basidiomycota increase over time, becoming most frequent at the advanced decomposition stage [48,51,[89][90][91].…”
Section: Fungal Diversitysupporting
confidence: 92%
“…Fungi are the key players in litter decomposition and nutrient cycling owing to their ability to produce a wide range of extracellular enzymes which allow them to attack efficiently the recalcitrant lignocellulose matrix [44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, although the NMDS showed the fungal species composition changes among forests, the proportion of the different functional guilds looks quite consistent at the forest level. The observed compositional difference may be explained by site-level differences in the climate and edaphic factors, that are known to influence fungal structures in forest systems 60 . The differences in the fungal communities among the three studied forests underlines the conservational value of each particular fragment of the church forest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reveal probable mis-annotations, our survey also highlights the presence of ciliates, especially hypotrichs, in the environment/matrices generally studied for the presence of fungi. Intriguingly, most of these environment/matrices represent human byproducts, e.g., compost 96 , forest soil 97,98 , or even extreme environment, e. g., crater lake 99 and permafrost 100 , which should deserve further investigations from the community of ciliate taxonomists. Dedication We dedicate this species to Prof. Fukang Gu, School of Life Sciences, East China Normal University, for his dedication to the cytology of protozoan and also as a small token of appreciation for his kind guide and support for Ms. Wanying Liao during her master study.…”
Section: Morphogenetic Comparison With Related Taxa the Most Importamentioning
confidence: 99%